Physical activity and bullying in adolescents with overweight and obesity - McCoy, S.M.; Rupp, K. (International Journal of Bullying Prevention, 2024)
Background: The relationship between physical activity (PA) and bullying behaviors is unclear among adolescents with overweight/obesity (OW/OB). The current study examined the likelihood of engaging in bullying behaviors by differing physical activity behaviors in adolescents with OW/OB. Method: Analyses included 9114 adolescents with OW/OB, ages 10–17 years, from the combined 2018–2019 National Survey of Children’s Health. Adolescents were grouped by PA level (0 days, 1–3 days, 4–6 days, every day); outcome variables included bullying behaviors (perpetrator, victim, both, or neither), sport participation, behavioral conduct problems, depression, difficulty making new friends, and excessive arguing. Separate adjusted logistic regression models assessed the odds of each outcome comparing differing PA levels. Results: Compared to their inactive peers, adolescents with OW/OB that engaged in at least 1 day of PA were significantly less likely to be victims of bullying (OR = 0.80; 95% CI (0.68, 0.93)) and to be both a bully perpetrator and victim (OR = 0.77; 95% CI (0.64, 0.94)). Participation in sports significantly increased the likelihood of being a bully perpetrator (OR = 1.50; 95% CI (1.06, 2.11)) and decreased the likelihood of being a bully victim (OR = 0.83; 95% CI (0.75, 0.92)) in adolescents with OW/OB. Additionally, adolescents with OW/OB that participated in PA were less likely to experience adverse psychosocial outcomes. Conclusions: Findings suggest PA participation (≥ 1 day/week) may reduce the likelihood of bully victimization and both (perpetration and victimization) and attenuate adverse psychosocial outcomes in adolescents with OW/OB. However, sport participation may increase bully perpetration while decreasing bully victimization in adolescents with overweight/obesity. © The Author(s), under exclusive licence to Springer Nature Switzerland AG 2024.
Keywords: Adolescence; Bullying; Obesity; Physical activity; dept.hms; peer-reviewed